Enantioseparation and Determination of Mephedrone and Its Metabolites by Capillary Electrophoresis Using Cyclodextrins as Chiral Selectors - Řezanka, Pavel (Molecules, 2020)
Mephedrone, a psychoactive compound derived from cathinone, is widely used as a designer drug. The determination of mephedrone and its metabolites is important for understanding its possible use in medicine. In this work, a method of capillary electrophoresis for the chiral separation of mephedrone and its metabolites was developed. Carboxymethylated β-cyclodextrin was selected as the most effective chiral selector from seven tested cyclodextrin derivates. Based on the simplex method, the optimal composition of the background electrolyte was determined: at pH 2.75 and 7.5 mmol·L(−1) carboxymethylated β-cyclodextrin the highest total resolution of a mixture of analytes was achieved. For mephedrone and its metabolites, calibration curves were constructed in a calibration range from 0.2 to 5 mmol·L(−1); limits of detection, limits of quantification, precision, and repeatability were calculated, and according to Mandel’s fitting test, the linear calibration ranges were determined.